HIV-Infected Former Plasma Donors in Rural Central China: From Infection to Survival Outcomes, 1985–2008 - Dou, Zhihui; Chen, Ray Y.; Wang, Zhe; Ji, Guoping; Peng, Guoping; Qiao, Xiaochun; Fu, Jihua; Meng, Xiangdong; Bulterys, Marc; Ma, Ye; Zhao, Yan; Wang, Ning; et al. (PloS one, 2010)
The HIV epidemic among former plasma donors (FPDs) in rural Central China in the early-mid 1990s is likely the largest known HIV-infected cohort in the world related to commercial plasma donation but has never been fully described. The objectives of this study are to estimate the timing and geographic spread of HIV infection in this cohort and to demonstrate the impact of antiretroviral therapy on survival outcomes. HIV-infected FPDs were identified using the national HIV epidemiology and treatment databases. Locations of subjects were mapped. Dates of infection and survival were estimated using the midpoint date between initial-final plasma donation dates from 1985-2008 among those with plasma donation windows ≤2 years. Among 37,084 FPDs in the two databases, 36,110 were included. 95% were located in focal areas of Henan Province and adjacent areas of surrounding provinces. Midpoint year between initial-final plasma donation dates was 1994 among FPDs with known donation dates. Median survival from infection to AIDS was 11.8 years and, among those not treated, 1.6 years from AIDS to death. Among those on treatment, 71% were still alive after five years. Using Cox proportional hazard modeling, untreated AIDS patients were 4.9 times (95% confidence interval 4.6-5.2) more likely to die than those on treatment. The epidemic of HIV-infected FPD in China was not widespread throughout China but rather was centered in Henan Province and the adjacent areas of surrounding provinces. Even in these areas, infections were concentrated in focal locations. Overall, HIV infections in this cohort peaked in 1994, with median survival of 13.4 years from infection to death among those not treated. Among AIDS patients on treatment, 71% were still alive after five years.